2023
DOI: 10.1136/jitc-2023-007802
|View full text |Cite
|
Sign up to set email alerts
|

MDSCs-derived GPR84 induces CD8+T-cell senescence via p53 activation to suppress the antitumor response

Jinyan Liu,
Jiayin Liu,
Guohui Qin
et al.

Abstract: BackgroundsG-protein-coupled receptor 84 (GPR84) marks a subset of myeloid-derived suppressor cells (MDSCs) with stronger immunosuppression in the tumor microenvironment. Yet, how GPR84 endowed the stronger inhibition of MDSCs to CD8+T cells function is not well established. In this study, we aimed to identify the underlying mechanism behind the immunosuppression of CD8+T cells by GPR84+MDSCs.MethodsThe role and underlying mechanism that MDSCs or exosomes (Exo) regulates the function of CD8+T cells were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Research has indicated that exosomal delivery of high levels of programmed death-ligand 1 (PD-L1) can lead to macrophage dysfunction, indirectly impairing T-cell function [ 95 ]. Additionally, exosomes from myeloid-derived suppressor cells (MDSCs) can induce T-cell senescence through the P53 pathway [ 96 ]. Therefore, we speculate that exosomes may be involved in delivering immunosuppressive cytokines, upregulating inhibitory receptors or ligands, and increasing the proportion of regulatory cells.…”
Section: Hbv Modifies Exosomes To Reshape the Host Immune Microenviro...mentioning
confidence: 99%
“…Research has indicated that exosomal delivery of high levels of programmed death-ligand 1 (PD-L1) can lead to macrophage dysfunction, indirectly impairing T-cell function [ 95 ]. Additionally, exosomes from myeloid-derived suppressor cells (MDSCs) can induce T-cell senescence through the P53 pathway [ 96 ]. Therefore, we speculate that exosomes may be involved in delivering immunosuppressive cytokines, upregulating inhibitory receptors or ligands, and increasing the proportion of regulatory cells.…”
Section: Hbv Modifies Exosomes To Reshape the Host Immune Microenviro...mentioning
confidence: 99%
“…While the exact impact of cellular senescence within MDSCs has yet to be explored, these cells are highly associated with the onset of age-related immune changes by modulating senescence phenotypes in surrounding cells. For example, one study found that MDSCs prevent senescence in cardiac myofibroblasts, resulting in age-related cardiac fibrosis [124]. Another study demonstrated that a subpopulation of MDSCs could induce senescence in CD8+ T-cells through exosomal transfer of GPR84, a G-protein coupled receptor that signals through p53 to halt cell proliferation [125].…”
Section: Senescence In the Immune Compartmentsmentioning
confidence: 99%